Preference Towards Online Mode of Distance Education Courses–conjoint Analysis - Malarkodi, M.; Indumathi, V. M.; Praveena, S. (International Journal of Bio-resource and Stress Management, 2018)
In India online education was in its primitive stage. Though, maximum educational institutes had adopted the process of online admission and online result announcement, but the method of teaching through online was relatively slow in India. It was important for the universities to understand the preference towards online learning. Conjoint analysis was used to frame the preferences of sample respondents on the design of online mode of distance education. Conjoint analysis was utilized to know about the preference status among the distance learning courses offered by Tamil Nadu Agricultural university, the sample size consists of 90 Agri student and 90 non Agri student respondents. Course, Period, Format, and Duration attributes were selected for the experiment. From the results it was observed that the respondents preferred to do a certificate courses in PDF and Video format with 2 hrs of time duration for the period of one month. Majority of the agricultural students preferred PG degree courses whereas the non-agricultural students preferred certificate courses. Both agricultural and non-agricultural students preferred to do the computer related tasks. Among all the respondents, flexibility of study location was the major reason for the students to prefer online education followed by flexibility of study time and less need to go to campus. It was observed that respondents were not sure about the problems in distance education.